Altered Cholinergic Innervation in De Novo Parkinson's Disease with and Without Cognitive Impairment. Issue 4 (17th January 2022) - van der Zee, Sygrid; Kanel, Prabesh; Gerritsen, Marleen J.J.; Boertien, Jeffrey M.; Slomp, Anne C.; Müller, Martijn L.T.M.; Bohnen, Nicolaas I.; Spikman, Jacoba M.; van Laar, Teus
Abstract: Background: Altered cholinergic innervation plays a putative role in cognitive impairment in Parkinson's disease (PD) at least in advanced stages. Identification of the relationship between cognitive impairment and cholinergic innervation early in the disease will provide better insight into disease prognosis and possible early intervention. Objective: The aim was to assess regional cholinergic innervation status in de novo patients with PD, with and without cognitive impairment. Methods: Fifty‐seven newly diagnosed, treatment‐naive, PD patients (32 men, mean age 64.6 ± 8.2 years) and 10 healthy controls (5 men, mean age 54.6 ± 6.0 years) were included. All participants underwent cholinergic [ 18 F]fluoroethoxybenzovesamicol positron emission tomography and detailed neuropsychological assessment. PD patients were classified as either cognitively normal (PD‐NC) or mild cognitive impairment (PD‐MCI). Whole brain voxel‐based group comparisons were performed. Results: Results show bidirectional cholinergic innervation changes in PD. Both PD‐NC and PD‐MCI groups showed significant cortical cholinergic denervation compared to controls ( P < 0.05, false discovery rate corrected), primarily in the posterior cortical regions. Higher‐than‐normal binding was most prominent in PD‐NC in both cortical and subcortical regions, including the cerebellum, cingulate cortex, putamen, gyrus rectus, hippocampus, and amygdala. Conclusion: Altered cholinergic innervation is already present in de novo patients with PD. Posterior cortical cholinergic losses were present in all patients independent of cognitive status. Higher‐than‐normal binding in cerebellar, frontal, and subcortical regions in cognitively intact patients may reflect compensatory cholinergic upregulation in early‐stage PD. Limited or failing cholinergic upregulation may play an important role in early, clinically evident cognitive impairment in PD. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society